Bioactive Potential of Endophytic Fungi from the Genus Aspergillus: A Comprehensive Review of Secondary Metabolites and Their Biological Activities - jumrah, elfira (Hayyan Journal, 2025)
This review provides a comprehensive synthesis of current knowledge on the bioactive potential of endophytic fungi belonging to the genus Aspergillus, emphasizing their secondary metabolites and associated biological activities. A systematic literature search was conducted across major scientific databases, including Scopus, Web of Science, PubMed, ScienceDirect, and Google Scholar, covering publications from January 2020 to October 2025. Studies were selected based on inclusion criteria focusing on the isolation, metabolite characterization, and bioactivity evaluation of endophytic Aspergillus species. Relevant data on fungal species, host plants, metabolite classes, and biological functions were extracted, organized, and analyzed qualitatively using a thematic and comparative approach. The analysis revealed that Aspergillus species are prolific producers of diverse secondary metabolites such as alkaloids, polyketides, terpenoids, xanthones, and peptides, exhibiting a broad range of biological activities including antimicrobial, antioxidant, anticancer, anti-inflammatory, antifungal, and antiparasitic effects. Key compounds such as gliotoxin, terrein, and vitexin demonstrate strong pharmacological properties and highlight the genus’s biotechnological significance. Overall, endophytic Aspergillus species represent an underexploited reservoir of natural bioactive compounds with high pharmaceutical and industrial relevance. Future research integrating genomics, metabolomics, and bioengineering is essential to unlock their full biosynthetic potential and advance sustainable drug discovery.